Impact of Auto-Rickshaw Service on the Livelihood of Chauffeurs' Household, Baglung, Nepal (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This research paper investigates the socioeconomic background and survival issues of auto rickshaw drivers in Baglung Bazaar using both quantitative and qualitative methods focusing descriptive and analytical research design. Survey, observation, and interview data were collected from 30 auto-drivers using random sampling, out of 98 auto-drivers. The aim is to provide voices in favor of legalizing rickshaws and e-rickshaws in the city, as well as to present policy suggestions on enhancing safety and efficiency. The rapid expansion of the rickshaw fleet in Baglung has caused earnings to dwindle and there are more traffic problems due to intense competition. If rickshaws are properly regulated, they would contribute greatly to city planning, generate government income, and improve transportation infrastructure. The study evaluated the socio-economic impact of diesel and battery rickshaws and determined that 80% of drivers are content with their occupation. At Baglung, when there were 20-25 autos, auto-drivers were earning more, but now there are 98 autos with unhealthy competition and reduced income there. So, the government should create regulations and laws. The findings revealed that auto driving job generate stress but lack a significant impact on job satisfaction. Income is uncertain and relies on the workers' performance; however, job satisfaction has a strong impact on employee performance directly, and job stress has a direct impact on employee performance in relation to job satisfaction. The current study will be helpful to future researchers and policymakers who are facing this problem.